Hydrothermal preparation of visible-light-driven Br-doped Bi2WO6 photocatalyst - Dumrongrojthanath P. (2017)
© 2017 Elsevier B.V. Bi 2 WO 6 loaded with 0–3 wt% Br was hydrothermally prepared and further characterized by XRD, Raman spectroscopy, TEM, SAED and XPS. In this research, both doped and un-doped samples were uniform orthorhombic Bi 2 WO 6 nanoplates. Their photocatalysis was evaluated through photodegradation of rhodamine B under visible radiation. Bi 2 WO 6 loaded with 3 wt% Br has the highest activity and can be used as a visible-light-driven photocatalyst.